2003
DOI: 10.1029/2001jb000523
|View full text |Cite
|
Sign up to set email alerts
|

Fractal pore structure of sedimentary rocks: Simulation by ballistic deposition

Abstract: [1] Experimental studies show that porous sedimentary rocks have a fractal pore-grain interface. The bidisperse ballistic deposition model (BBDM) generates a porous structure by computer simulation. The model is able to reproduce the behavior of several macroscopic properties of sedimentary rocks quite well. In the present paper we show that the microstructure of the pore space created in BBDM is also realistic. Two-point correlations of the pore space agree qualitatively with results for real rocks, and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 22 publications
0
49
0
Order By: Relevance
“…These approaches include the generation of regular pore networks (e.g., Berkowitz and Ewing, 1998), networks developed according to morphologically determined parameters of a soil (Vogel, 2000), the simulation of sedimentation processes (Dutta and Tarafdar, 2003), and the use of fractal models. For the latter, a minimum requirement for the applicability of the model is that the natural porous medium exhibits a self-similar scaling, described by its fractal dimension.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches include the generation of regular pore networks (e.g., Berkowitz and Ewing, 1998), networks developed according to morphologically determined parameters of a soil (Vogel, 2000), the simulation of sedimentation processes (Dutta and Tarafdar, 2003), and the use of fractal models. For the latter, a minimum requirement for the applicability of the model is that the natural porous medium exhibits a self-similar scaling, described by its fractal dimension.…”
Section: Introductionmentioning
confidence: 99%
“…We refer to this model as the Relaxed Bidisperse Ballistic Deposition Model (RBBDM). In an earlier study (Dutta and Tarafdar, 2003), the authors have shown that the sample attains a constant porosity only after a sufficient number of grains (depending on sample size) have been deposited to overcome substrate effects. Here, a 128 Â 1000 size sample was generated.…”
Section: Simulationmentioning
confidence: 98%
“…(2). The details of the generation of the porous rock sample are given in Dutta and Tarafdar (2003) and Sadhukhan et al (2007). Above the percolation threshold, the simulated structure has at least one connected pore structure.…”
Section: Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Much work has been done in this direction (Dasgupta et al . 2000; Dutta & Tarafdar 2003; Manwart et al . 2000; Øren & Bakke 2003; Pape et al .…”
Section: Introductionmentioning
confidence: 99%